A Cost Calculation Framework for Fuel Transport Tariffs Using Multi-Vessel Waterway Operations in Remote and Underdeveloped Areas of Indonesia - Lutfi Bahroni; Alvian Pratama; Very Aryanto (International Journal Labs, 2026)
Fuel distribution in remote and underdeveloped regions of Indonesia faces significant challenges due to complex geographical conditions, diverse transportation modes, and inconsistent tariff calculation mechanisms. These challenges may affect the efficiency, transparency, and sustainability of the national fuel supply system, particularly within the BBM Satu Harga program. This study aimed to develop a standardized cost calculation framework for fuel transportation tariffs using multi-vessel waterway operations to support more accurate, equitable, and risk-based tariff determination. The research employed a mixed-method approach combining qualitative and quantitative methods through regulatory analysis, field data collection, route identification, cost component assessment, and simulation modeling. Data were obtained from service providers, operational regions, and relevant institutional sources, followed by the development of a Microsoft Excel-based tariff calculation framework. The results showed that the proposed framework successfully integrated six major cost components, including vessel costs, own-use fuel consumption, packaging, human resources, administrative and certification costs, and overhead expenses. The framework also incorporated load factor mechanisms, route-based adjustment factors, and safety incentives to accommodate operational risks and geographical variations. Simulation results across several regions demonstrated that the proposed tariffs were generally consistent with existing contract tariffs, while differences were primarily attributed to incomplete cost structures, negotiation-based pricing, and variations in vessel specifications. This study concluded that the developed framework provided a comprehensive and transparent approach for standardizing fuel transport tariffs and improving distribution efficiency in remote areas of Indonesia.